A synDNA vaccine delivering neoAg collections controls heterogenous, multifocal murine lung and ovarian tumors via robust T cell generation - Bhojnagarwala, Pratik S. (Mol Ther Oncolytics, 2021)
Neoantigens are tumor-specific antigens that arise due to somatic mutations in the DNA of tumor cells. They represent ideal targets for cancer immunotherapy since there is minimal risk for on-target, off-tumor toxicities. Additionally, these are foreign antigens that should be immunogenic due to lack of central immune tolerance. Tumor neoantigens are predominantly passenger mutations, which do not contribute to tumorigenesis. In cases of multi-focal or metastatic tumors, different foci can have significantly different mutation profiles. This suggests that it is important to target as many neoantigens as possible to better control tumors and target multi-focal tumors within the same patient. Herein, we report a study targeting up to 40 neoantigens using a single DNA plasmid. We observed significant plasticity in the epitope strings arranged in the vaccine with regard to immune induction and tumor control. Different vaccines elicited T cell responses against multiple epitopes on the vaccine string and controlled growth of multi-focal, heterogeneous tumors in a therapeutic tumor challenge. Additionally, the multi-epitope antigens induced long-term immunity and rejected a tumor re-challenge several weeks after the final vaccination. These data provide evidence that DNA-encoded long antigen strings can be an important tool for immunotherapeutic vaccination against neoantigens with implications for other in vivo-delivered antigen strings.